Enhanced arc magmatic productivity of the Western Pacific island arcs deduced from gravity-derived arc crustal growth rates - Parcutela, N. E.; Austria, R. S.; Dimalanta, C. B.; Valera, G. T. V.; Gabo-Ratio, J. A. S.; Payot, B. D.; Armada, L. T.; Sangalang, K. J. F.; Yumul, G. P. (Frontiers in Earth Science, 2023)
Island arcs are postulated as the juvenile components that contribute to the growth of continental crust. Growth rates of arc crusts were previously computed using crustal thicknesses derived from seismic data. As a consequence, crustal growth rates of oceanic island arcs are also constrained by the limited seismic data availability. This work presents the first comparison of gravity-derived magmatic growth rates of western Pacific oceanic island arcs. We used the statistical correlation between Bouguer anomalies and seismic-derived crustal thicknesses to generate an empirical formula. The new empirical formula was utilized to estimate the crustal thicknesses of oceanic island arcs using Bouguer anomalies from the EGM2008 global gravity model. The resulting crustal thicknesses were employed to compute the magmatic growth rates of western Pacific island arcs and the Philippine island arc system. The latest magmatic growth rate estimates show that the magmatic productivity of western Pacific island arcs, which are directly associated with Pacific Plate subduction, is significantly higher (28 to 60 km3/km/m.y.). The growth rate of the Pacific island arcs is higher compared to the magmatic growth rate computed for the other oceanic island arcs (12 to 25 km3/km/m.y.), which are derived from the subduction of other oceanic lithospheres (i.e., the Philippine Sea Plate; Caribbean Sea Plate; and Eurasia-South China Sea slabs). This is attributed to the variation in the ages of the subducting plates. The Pacific Plate, being older, is associated with higher degrees of serpentinization and sediment cover, which introduce more volatiles inducing more robust partial melting of the mantle wedge.